If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -6 = 14x + -14 Reorder the terms: -6 + 6x = 14x + -14 Reorder the terms: -6 + 6x = -14 + 14x Solving -6 + 6x = -14 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -6 + 6x + -14x = -14 + 14x + -14x Combine like terms: 6x + -14x = -8x -6 + -8x = -14 + 14x + -14x Combine like terms: 14x + -14x = 0 -6 + -8x = -14 + 0 -6 + -8x = -14 Add '6' to each side of the equation. -6 + 6 + -8x = -14 + 6 Combine like terms: -6 + 6 = 0 0 + -8x = -14 + 6 -8x = -14 + 6 Combine like terms: -14 + 6 = -8 -8x = -8 Divide each side by '-8'. x = 1 Simplifying x = 1
| -14-r-6r=r+8 | | 2210=r(34) | | 42=2+6 | | 9-4b=6-5b | | 6-4(5+3y)=0 | | 8-1/2(-m-1) | | M+6=2m+11 | | 7v-15+7v=7v+48 | | 23=32x-425 | | 1680=336t | | 5(9x+6)=45x-4 | | 0.5x=-70 | | 3lx-1l=15 | | (3x+25)+(x-5)+x=180 | | -5-8=-13x-4 | | 2x+105=-3x+130 | | 7n+3=8+8n | | f(a+1)=(a+1)+8 | | a-43+a-43+w+43=a | | 9x+8=9x-2 | | 15*3-25+10= | | u+u+3=u+46 | | 3x-5(x-4)=-5+4x+13 | | 3x+9x-7=3(4x+4) | | 8t+40+16t-49=18t+23 | | 18x-12=3x^2 | | 7+6*2-2+8= | | 7a+21b=110 | | 2(1/6)*(3/26) | | d=85(4h) | | 34+32a-50=23a+26 | | 6x+6=6x+5 |